Wideband and Multiband Antenna Design and Fabrication for Modern Wireless Communications Systems - Adit Kurniawan; Salik Mukhlishin (Journal of ICT Research and Applications, 2013)
One of the major challenges due to spectrum scarcity in modern wireless communication is on antenna design that can serve a non-contagious frequency spectrum. In this paper, wideband and multiband design approaches are proposed to produce antennas that can serve various wireless technologies using different frequencies from 2.3 to 6.0 GHz, covering WiFi frequencies at 2.4-2.48 GHz, 5,15-5,35 GHz and 5,725-5,825 GHz, as well as WiMax frequencies at 2.3-2.4 GHz, 2.495-2.695 GHz, 3.3-3.8 GHz, and 5.25-5.85 GHz. The wideband and multiband antenna were implemented on an 0.8 mm thick of FR4 epoxy dielectric substrate with permittivity Îµr="4".3. The return loss of 10 dB can be achieved for 2.3 to 6 GHz in wideband antenna, and a tripe band of 2.3-2.8 GHz, 3.3-3.7 GHz, and above 4.6 GHz in multiband antenna. The gain of both antennas increases almost linearly from 0 dB at 2.3 GHz to around 4.5 dB at 6 GHz, except for the stop band at 2.8-3.3 GHz which has a significant drop of gain, corresponding to the stop frequency band. Antenna radiation pattern is bidirectional at x-y plane and nearly omnidirectional at y-z plane, and shows a similar patern for both wideband and multiband design approaches.